INCIDENCE OF ABNORMAL CORONARY ARTERY ORIGINS IN WORKING-AGE PATIENTS WITH CORONARY HEART DISEASE - Khasanjanova Farida Odilovna; Sadikov Zafar (Scholar Express Journals, 2025)
This scientific work studied the incidence of abnormal origins of the coronary arteries in patients with coronary artery disease of working age. The study was conducted from January 2024 to December 2024 and 5170 coronary angiographic studies were performed, among which 35 patients were found to have abnormal origins of the coronary arteries. The average age of patients was 40 years (from 19 to 75 years), 23 patients were men and 12 patients were women. According to coronary angiography studies, various types of abnormal origins of the coronary arteries were detected in 35 patients: abnormal origin of the circumflex artery (CA) from the right coronary artery (RCA) was detected in 12 patients, abnormal origin of the RCA from the aorta above the sinus of Valsalva (SV) was determined in 9 patients, abnormal origin of the RCA from the left SV was detected in 6 patients, abnormal origin of the OB from the right SV was determined in 4 cases, abnormal origin of the anterior descending artery (LDA) from the RCA was noted in 3 patients, and a single coronary artery (SCA) was diagnosed in only one patient.
Keywords: coronary artery disease; anomaly; coronary artery